Nghiệm của hệ phương trình \(\left\{ \begin{array}{l}x + 2y = 1 + i\\3x + iy = 2 - 3i\end{array} \right.\) là:

Câu hỏi :

Nghiệm của hệ phương trình \(\left\{ \begin{array}{l}x + 2y = 1 + i\\3x + iy = 2 - 3i\end{array} \right.\) là:

A. \(\left\{ \begin{array}{l}x = 1 + i\\y = i\end{array} \right.\).     

B. \(\left\{ \begin{array}{l}x = i\\y = 1 + i\end{array} \right.\). 

C. \(\left\{ \begin{array}{l}x = 1 - i\\y = i\end{array} \right.\).    

D. \(\left\{ \begin{array}{l}x = i\\y = 1 - i\end{array} \right.\). 

* Đáp án

C

* Hướng dẫn giải

\(\left\{ \begin{array}{l}x + 2y = 1 + i\\3x + iy = 2 - 3i\end{array} \right. \)

\(\Leftrightarrow \left\{ \begin{array}{l}x = 1 + i - 2y{\rm{       (1)}}\\3x + iy = 2 - 3i{\rm{   (2)}}\end{array} \right.\)

Thay (1) vào (2) ta được:

\(\begin{array}{l}3(1 + i - 2y) + iy = 2 - 3i\\ \Leftrightarrow ( - 6 + i)y =  - 1 - 6i\\ \Leftrightarrow y = \dfrac{{ - 1 - 6i}}{{ - 6 + i}}\\ \Leftrightarrow y = \dfrac{{\left( { - 1 - 6i} \right)\left( { - 6 - i} \right)}}{{36 - {i^2}}} = i\end{array}\)

Thay y = i vào (1) \( \Rightarrow x = 1 - i\)

Copyright © 2021 HOCTAP247